Households' Foreign Currency Borrowing in Central and Eastern Europe - Jarko Fidrmuc; Mariya Hake; Helmut Stix (Oesterreichische Nationalbank (OeNB), 2011)
Foreign currency loans represent an important feature of recent financial developments in CEECs. This might pose a serious challenge for macroeconomic stability. Against this background, the authors study the determinants of foreign currency loans of households, using data on the behavior of households in nine CEECs. Their results reveal that foreign currency loans are driven by households' lack of trust in the stability of the local currency and in domestic financial institutions. Moreover, special factors including remittances and expectations of euro adoption play an important role in selected regions. The financial crisis reduced foreign currency borrowing, but there is some indication this effect might be only temporary.
Keywords: G18; G21; C25; 330; Foreign currency loans; dollarization; euroization; monetary credibility; trust; CEEC